Exploring the Potential of Magnetic Fields on Plant Growth as Monitoring Agricultural Success: Exploring the Potential of Magnetic Fields on Plant Growth as Monitoring Agricultural Success - SAKTI KALISA SEFANDA; Vina Zulviana Nafilla; Probo Anggara; Sudarti; Kendid (Jurnal Agro Indragiri, 2025)
The physical field created by an electrically charged object is called an electromagnetic field. This research aims to determine the impact of using magnetic fields on crop productivity and quality in order to achieve success in agriculture. The type of research used is qualitative with the method of literature review or literature review relevant to the research title. The results showed that the comparison of several previous studies. The results of checking soil conditions using magnetics to increase agricultural yields and the potential influence of magnetic fields on plant growth. This research will provide readers with a deeper understanding of how magnetic fields can affect plants.